On the Generalized Reflective Function of the Three-Degree Polynomial Differential System - Jian Zhou; Shiyin Zhao (Journal of Function Spaces)
The structure of the generalized reflective function of three-degree polynomial differential systems is considered in this paper. The generated results are used for discussing the existence of periodic solutions of these systems.